2004
DOI: 10.1002/cne.20322
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cux‐1 and Cux‐2 in the subventricular zone and upper layers II–IV of the cerebral cortex

Abstract: Little is known about how neurons in the different layers of the mammalian cerebral cortex are specified at the molecular level. Expression of two homologues of the Drosophila homeobox Cut gene, Cux-1 and Cux-2, is strikingly specific to the pyramidal neurons of the upper layers (II-IV) of the murine cortex, suggesting that they may define the molecular identity of these neurons. An antibody against Cux-1 labels the nucleus of most of the postmitotic upper layer neurons but does not label parvoalbumin-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
367
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(405 citation statements)
references
References 47 publications
32
367
1
1
Order By: Relevance
“…From P21, Cux-2 mRNA was also expressed in the cingulate cortex ( Fig. 1F) (Nieto et al, 2004). A strong expression of Cux-2 was also noted at the level of the claustrum (not shown).…”
Section: Cux-1 and Cux-2 Mrna Expression In Postnatal Cerebral Cortexmentioning
confidence: 82%
See 1 more Smart Citation
“…From P21, Cux-2 mRNA was also expressed in the cingulate cortex ( Fig. 1F) (Nieto et al, 2004). A strong expression of Cux-2 was also noted at the level of the claustrum (not shown).…”
Section: Cux-1 and Cux-2 Mrna Expression In Postnatal Cerebral Cortexmentioning
confidence: 82%
“…Cux-1 and Cux-2 are early markers of neuronal differentiation; both genes are expressed in postmitotic neurons at early embryonic stages. Cux-1 and Cux-2 are also expressed in proliferative zones of the cerebral cortex, with selective Cux-2 expression in SVZ progenitors (Nieto et al, 2004;Zimmer et al, 2004). Interestingly, Pax6 mutant mice show a loss of Cux-2-positive cells in the SVZ as well as a loss of Cux-1 and Cux-2 in the upper layer neurons, supporting the SVZ origin of the glutamatergic neurons in layers II-IV of the neocortex (Nieto et al, 2004;Zimmer et al, 2004).…”
mentioning
confidence: 81%
“…However, this view has been challenged first based on histological studies [16], and subsequently by the observation that SVZ cells show patterns of gene expression that are echoed by those in upper layer neurons. For example, the noncoding RNA Svet1 and several homodomain genes, including Cux1 and Cux2 are expressed both in the SVZ and in layers 2-4 [17,18]. These corresponding patterns of gene expression suggested that upper layer neurons might be derived from the SVZ.…”
Section: Cellular Studies Of Cell Fate Determination Suggest a Progrementioning
confidence: 99%
“…IPC then divides symmetrically to generate two neurons or two additional IPCs (Wu and Cepko, 1993;Haubensak et al, 2004;Miyata et al, 2004;Noctor et al, 2004Noctor et al, , 2007a. Therefore, embryonic SVZ is increasingly considered as a major site of neurogenesis, whereas symmetric division is recognized to transit amplifying division (Miyata et al, 2001(Miyata et al, , 2004Tarabykin et al, 2001;Smart et al, 2002;Nieto et al, 2004;Noctor et al, 2004Noctor et al, , 2007bZimmer et al, 2004;Martínez-Cerdeño et al, 2006).…”
Section: Rg Cell Division In Neocortical Developmentmentioning
confidence: 99%